2007
DOI: 10.1152/jn.00401.2007
|View full text |Cite
|
Sign up to set email alerts
|

EEG Sharp Waves and Sparse Ensemble Unit Activity in the Macaque Hippocampus

Abstract: Neural unit activity and EEGs were recorded from inferior temporal regions of three rhesus macaques chronically implanted with "hyperdrives" holding 12 individually movable tetrodes. Recordings were made from each monkey over a period of approximately 3 mo, while the electrodes were moved by small increments through the hippocampus and neighboring structures. After recording, the monkeys were necropsied, and the brains were sectioned and Nissl-stained, permitting identification of individual electrode tracks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
124
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(150 citation statements)
references
References 61 publications
(84 reference statements)
24
124
0
Order By: Relevance
“…Various researchers have found significant sharp waves in monkeys and humans. [15,16] It seems that appearance of sharp wave during odor administration, in the temporal region perhaps indicates their association with memory as shown in previous research. [17] The EEG abnormalities (slowing and sharp waves) were mainly observed in right temporal region and occasionally in frontotemporal, centro-parieto-temporal, and centro-parietal regions.…”
Section: Discussionsupporting
confidence: 59%
“…Various researchers have found significant sharp waves in monkeys and humans. [15,16] It seems that appearance of sharp wave during odor administration, in the temporal region perhaps indicates their association with memory as shown in previous research. [17] The EEG abnormalities (slowing and sharp waves) were mainly observed in right temporal region and occasionally in frontotemporal, centro-parieto-temporal, and centro-parietal regions.…”
Section: Discussionsupporting
confidence: 59%
“…Such oscillations have been reported not only in rats (Vanderwolf, 1969) but also in a wide range of other mammals including mice (Buzsaki et al, 2003), bats (Ulanovsky and Moss, 2007), monkeys (Skaggs et al, 2007), and humans (Kahana et al, 1999). Sharp-wave related ripple activity was also first reported in the rat (Buzsaki, 1986) but has since been observed in cats (Grenier et al, 2003), monkeys (Skaggs et al, 2007), and humans (Bragin et al, 1999). Altogether, the many similarities in connectivity and network activity suggest that hippocampal areas perform similar computational functions across a wide range of mammalian species.…”
Section: Introductionmentioning
confidence: 91%
“…Experiments on cats and monkeys have extended detailed investigation of HFOs to more highly developed mammals (Grenier et al, 2001;Skaggs et al, 2007). Recordings from cats demonstrated that HFOs with ripple frequency occur during active network states and when the membrane potential of cortical neurons is depolarized.…”
Section: Preparations and Physiological Oscillationsmentioning
confidence: 99%
“…However, the level of the membrane potential is not the sole factor; in normal behavioural conditions the maximal power of cortical ripples occurs during active "UP" phases of slow-wave sleep, smaller during passive wakefulness and REM sleep and lowest (virtually absent) during silent "DOWN" phases of slow wave sleep (Grenier et al, 2001). In hippocampus of both rats and monkeys, ripples are typically recorded during inactive, drowsy or sleeping behavioral states, all of which are associated with increased hippocampal pyramidal cell activity (Skaggs et al, 2007;Ylinen et al, 1995).…”
Section: Preparations and Physiological Oscillationsmentioning
confidence: 99%